La perception des Alliés dans la presse de la Résistance française (1940-1944) - Guérard-Bigras, Laurie (Université de Montréal, 2023)
The French Resistance press was born following the defeat of France and the signing of the armistice with Germany in June 1940. It embodied the will of some French citizens to refuse the occupation and to represent an alternative to Vichy France. In addition to countering official propaganda, the underground newspapers published their vision of the France to be rebuilt in the post-war period. Our master’s thesis analyzes the perception of the Allies in the French Resistance press between 1940 and 1944, in order to highlight the extent to which France's place in the world is visible through the vision shown of the three great powers, who are allies, but who could represent threats after the Liberation. The portraits of the Allies allow us to analyze and understand the plans and concerns of the Resistance. Based on a discursive, diachronic and thematic analysis of the clandestine newspapers, we are able to show that the perception of the Allies evolves during the course of the war, moving from a generally positive view between 1940 and 1942 to a more critical perception in the spring of 1944. At the beginning of the war, the Resistance offered a portrait of the Allies based on their military strength. Nevertheless, from 1943 onwards, it had to protect the population and gain legitimacy. This change strengthened the Resistance and allowed it to gradually impose itself as the authority protecting French interests in the face of Allies whose postwar intentions were increasingly criticized.
Keywords: =CL; Allies; Alliés; European history / Histoire de l’Europe (UMI : 0335); France; Resistance; Resistance press; Résistance intérieure; Seconde Guerre mondiale; World War II; international relations; presse de la Résistance; relations internationales